Non-atopic asthma in children is related to maternal bronchial hyperreactivity - CEYHAN, BERRİN (WILEY, 2008)
Data on the pathogenic mechanisms underlying the development of non-atopic asthma in children are scarce. Our aim was to evaluate the association and compare the atopic status, pulmonary functions, bronchial hyperresponsiveness and serum total immunoglobulin E (IgE) levels of parents of atopic and non-atopic asthmatic children by using objective methods. Fifty-one asthmatic children aged 4-16 yr and their parents were included into the study. Initially the American Thoracic Society's Respiratory Disease questionnaire inquiring data on symptoms of asthma, rhinitis and past medical history was filled in. Afterwards, skin prick test with aeroallergens, pulmonary function and methacholine bronchial provocation tests and serum sampling for total IgE level determinations were carried out. Bronchial hyperresponsiveness to methacholine was significantly more common in the mothers of non-atopic children compared to those of atopic ones, although no significant difference was observed in the skin prick test reactivity, pulmonary function test parameters and serum IgE levels. Questionnaire data revealed that the presence of asthmatic symptoms such as wheezing and phlegm and doctor-diagnosed asthma were more common in the mothers of non-atopic children. Meanwhile, asthmatic symptoms were also found to be significantly more common in fathers of non-atopic children. Logistic regression analyses revealed that maternal PC20 was the only predictive factor for the risk of displaying non-allergic asthma in children. The results demonstrate that among the risk factors studied, maternal bronchial hyperreactivity was associated with the development of asthma in non-atopic children.
Keywords: bronchial hyperresponsiveness; parental atopy; pediatric asthma; SERUM IGE LEVELS; RISK-FACTORS; INHALANT ALLERGENS; INTRINSIC ASTHMA; GENETIC-FACTORS; CHILDHOOD; METHACHOLINE; REACTIVITY; ADAM33; ATOPY